Increasing Awareness of Disaster Preparedness: Online Modules for Pre-Clerkship Medical Students - Laryssa A. Patti; Norma Saks (Association of American Medical Colleges, 2013)
Abstract Introduction In 2003, the Expert Panel on Bioterrorism Education for Medical Students, an inter-professional task force convened by the Association of American Medical Colleges, recommended the inclusion of disaster preparedness training in the medical student curriculum. However, few medical schools include disaster preparedness topics in their curricula. This resource provides educational material on disaster preparedness for first- and second-year medical students. It includes three short modules on disaster preparedness topics, consisting of: (1) the Incident Command System, a tool used to organize emergency response (2) triage, a process of determining the priority of patient treatment based on the severity of their injuries, and (3) weapons of mass destruction, materials that can cause harm and damage to large numbers of people or structures. Methods The information in these modules is presented in separate 10-15 minute interactive online formats (45-60 minutes total), and can be used as a unit or individually. This resource includes a pre- and posttest for evaluation of student learning and a module evaluation form. Results Fifteen first- and second-year medical students at Robert Wood Johnson Medical School volunteered to use this resource. The modules were made available on the school's internal course management system and pre- and posttest results and survey information were collected anonymously through the system. Pre- and posttest scores indicated that students gained knowledge regarding the topics covered in the modules; average scores increased from 63% to 83% correct. Overall, students responded positively to the use of the online format as a way of providing information. Thirteen reported this being their first exposure to disaster preparedness topics during medical school. All reported that the material in the modules was easy to understand, and 14 would recommend the modules to a classmate. Ten participants reported feeling "more prepared to help in a disaster." Discussion Few medical schools include disaster preparedness topics in their curricula. This resource provides educational material on a number of disaster preparedness topics for first- and second-year medical students.